Analysis of Tempe Tofu Home Industry Standards on Occupational Safety Health (K3) Aspects in Purwodadi Village, Kuala Pesisir District, Naga Raya Regency - Muhammad Rizqi; Zakiyuddin Zakiyuddin (RADJA PUBLIKA, 2022)
Tofu and tempeh are foods derived from a variety of processed soybeans which have been famous foods among the public for a long time because the tariffs are relatively affordable and widely consumed by the public from various groups. Its existence has long been known and recognized as a healthy and nutritious food. A micro and macro industrial business must have K3 guidelines and K3 standards, although micro-enterprises such as tempeh tofu must also have standards that have been set Industrial work standards which refer to the K3 Law regarding K3 standards. This study focuses on analyzing the standards of the tempeh tofu home industry on occupational safety health (K3) aspects in Purwodadi village, Kuala Pesisir district, Naga Raya regency. This research describes a qualitative type of research. The sample in the study consisted of 14 informants accumulatively broken down from 7 main informants and 7 transmission informants. The measuring equipment used is in the form of literature studies, observations and interview guidelines. The data were analyzed using qualitative analysis whose results were presented in the form of a narrative( descriptive). The results of the study showed that applying assessment standards to buildings has not met the qualifications of businessworthy buildings. Conclusions of the study; each business is required to apply home industry standards and K3 aspects so that work productivity is good and guaranteed from work accidents.